2013
DOI: 10.1111/1754-9485.12106
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the lumbosacral plexus‐contouring protocol developed by Yi et al. (IJROBP 2012; 84: 376–82) for pelvic malignancies

Abstract: We conclude that the protocol developed by Yi et al. is a useful set of guidelines but suggest that additional at-risk components of the LSP also be contoured. We recommend that radiation oncologists practise 'nerve-sparing' radiotherapy by contouring LSPs, especially when using IMRT. We propose the term 'lumbosacral plexus regions' (LSPRs) to highlight the fact that LSPs are not always radiologically visible, only the regions where they are likely to be present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
2
8
2
Order By: Relevance
“…In the current study, LSP volume was observed to be 92.22-150.65 cm 3 (mean ± SD: 119.03 ± 15 cm 3 ), which was larger than those described by Yi et al [6] and Min et al [16], LSP volume: 71-138 cm 3 [6] and Tunio et al [18] study, where all patients had undergone pelvic irradiation using intensity-modulated radiotherapy (IMRT) technique. Min et al [16] in his study showed that the mean percentage of the LSP receiving 40…”
Section: Discussioncontrasting
confidence: 62%
“…In the current study, LSP volume was observed to be 92.22-150.65 cm 3 (mean ± SD: 119.03 ± 15 cm 3 ), which was larger than those described by Yi et al [6] and Min et al [16], LSP volume: 71-138 cm 3 [6] and Tunio et al [18] study, where all patients had undergone pelvic irradiation using intensity-modulated radiotherapy (IMRT) technique. Min et al [16] in his study showed that the mean percentage of the LSP receiving 40…”
Section: Discussioncontrasting
confidence: 62%
“…In the present study, we also noticed that risk for RILSP is more in patients older than 50 years of age and in those who are diabetic, although this difference was not significantly high in our cohort. In addition, the mean LSP dose (42.95 Gy) and mean V40 (52.8%), V50 (27.7%), V55 (0.31%), and V60 (0%) in our patients without RILSP indicates that mean dose lower than 45 Gy, V40 lower than 55%, V50 lower than 30%, V55 lower than 5%, and V60 lower than 0.5% for LSP during IMRT planning (especially focusing at the levels of P5, P6, P7, and P8) can significantly reduce the risk for RILSP, 7 as treatment for RILSP is usually symptomatic and often refractory.…”
Section: Discussionmentioning
confidence: 56%
“… 17 In our study, LSP volumes (mean volume, 93.2 cm 3 ) were consistent with those described by Yi et al (mean volume, 100 cm 3 ), which also validated this study; however, it is larger than those described by Min et al (mean volume, 40.9–58.4 cm 3 ). 6 , 7 The reason for larger volumes can be explained by the contouring of LSPRs when LSP was radiologically invisible in our series. Further in our study, the mean V50, V55, and V60 were slightly higher (ie, 36% versus 22%; 4.15% versus 0.5%; and 1.7% versus 0%), which can be explained by different IMRT techniques, different concurrent chemotherapy, parametrial boost in patients with cervical cancer, and higher point doses to P5, P6, P7, and P8.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Thus, in spite of the use of more advanced techniques of radiation therapy, such as intensity modulated radiotherapy (IMRT), this organ could undergo unwanted "dose dumping". Yi et al tried to standardize a method for contouring the lumbosacral plexus, but unfortunately, it is currently not adopted at most RT Departments, as well as in clinical trials (16,17).…”
Section: Current Strategies and Future Challengesmentioning
confidence: 99%